In-season in-field variable resistance training: effects on strength, power, and anthropometry of junior soccer players - Izadi, M.; Arazi, H.; Ramirez-Campillo, R.; Mirzaei, M.; Saidei, P. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Soccer players` leg muscular strength and power have been shown to be significant due to their association with soccer-specific performance including jumps, sprints, tackles and kicks. The aim of this study, therefore, was to examine the effects of an in-season in-field variable resistance training (VRT) program on strength, power, and anthropometry of junior soccer players. METHODS: A team of male soccer players were randomly assigned into Experimental (N.=10) and Control groups (N.=10). The Control group performed 8 weeks of soccer training alone. The Experimental group performed squat VRT using chains in addition to soccer training. Measures before and after training included squat strength, countermovement jump, and anthropometric estimation of thigh muscle cross sectional area (CSA). RESULTS: The VRT induced large improvements in absolute (34.45%; P=0.001; Cohen`s d=1.78) and relative strength to thigh muscle CSA (21.53%; P=0.002; Cohen`s d=1.04). Similarly, there were large (18.07%, P=0.007; Cohen`s d=1.5) increases in jump height and medium gains in absolute peak power output (16.13%; P=0.009; Cohen`s d=0.34) and relative peak power output to thigh muscle CSA (9.6%; P=0.002; Cohen`s d=0.31). Further, there was a medium increase (5.9%, P=0.03; Cohen`s d=0.36) in thigh muscle CSA. No significant changes were observed in the Control group. CONCLUSIONS: In-season in-field biweekly squat VRT enhanced strength and power measures in junior soccer players.